Differences in seeking breast cancer care between screening eligible versus ineligible Palestinian women - Mohamedraed Elshami; Maram Albandak; Mohammed Alser; Ibrahim Al-Slaibi; Faten Darwish Usrof; Malak Ayman Mousa Qawasmi; Islam Osama Ismail; Roba Jamal Ghithan; Heba Mahmoud Okshiya; Nouran Ramzi Shaban Shurrab; Ibtisam Ismail Mahfouz; Aseel AbdulQader Fannon; et al. (Scientific Reports)
Abstract In Palestine, breast cancer (BC) is the most prevalent cancer among women. This study explored the relationship between eligibility for BC screening and the time taken for seeking medical advice for possible BC symptoms. It also identified the barriers hindering early presentation among screening-eligible and ineligible Palestinian women. Palestinian females from governmental hospitals, primary healthcare centers, and diverse public venues across 11 governorates within Palestine were recruited using convenience sampling. A modified, translated-into-Arabic version of the BC Awareness Measure was utilized for data collection. The questionnaire comprised three sections: sociodemographic information, duration for seeking medical advice upon recognizing each of 13 possible BC symptoms, and barriers impeding early presentation. The final analysis included 2796 participants, with 2168 (77.5%) ineligible for BC screening and 628 (22.5%) eligible. The proportion of participants who would seek medical advice immediately varied depending on the nature of BC symptoms. Approximately half of participants in both the screening-eligible (n = 1097, 50.6%) and ineligible (n = 293, 46.7%) groups indicated that they would seek immediate medical advice for ‘lump or thickening in the breast.’ Similarly, about half of participants in both groups reported an inclination to seek immediate medical advice for ‘nipple discharge or bleeding’ (screening-eligible: n = 954, 44.0%; screening-ineligible: n = 280, 44.6%). Less than half of participants would seek immediate medical advice for other BC symptoms. Screening-eligible women were more likely to seek advice within a week for six out of 13 possible BC symptoms than screening-ineligible women. Among screening-eligible participants, 9.9% (n = 62) acknowledged a delay in seeking medical attention upon recognizing a potential BC symptom. Emotional barriers were most frequently reported, with ‘disliking the visit to healthcare facilities’ identified as the leading barrier among screening-eligible participants (n = 38, 61.3%). No association was found between BC screening eligibility and the total or type-specific number of reported barriers. Differences in immediate medical advice seeking for various BC symptoms were observed between screening-eligible and ineligible groups. Emotional barriers were the most prevalent in both groups. Tailored interventions to enhance BC awareness and address barriers to early presentation are essential.